Multi-objective assessment, optimization and application of a grid-connected combined cooling, heating and power system with compressed air energy storage and hybrid refrigeration. (15th October 2018) - Jiang, Runhua; Yin, Huibin; Chen, Baiman; Xu, Yongjun; Yang, Minlin; Yang, Xiaoxi
Highlights: A grid-connected CCHP system with CAES and hybrid refrigeration is proposed. A multi-objective assessment and optimization is presented. Each component capacity of the CCHP system is determined by optimization. A sensitivity analysis is conducted by the key parameters of the system. Performance comparison with conventional CCHP system has been done. Abstract: As one of attractive technology of energy conservation, combined cooling, heating and power (CCHP) system has brought about widespread attention. However, the variability of users demand has limited the application of CCHP system. To ensure stable and efficient operation, the compressed air energy storage is considered to be integrated with CCHP system. A grid-connected CCHP system with compressed air energy storage (CAES) and hybrid refrigeration is proposed in this paper. The power from grid is stored in CAES at off-peak time and released at on-peak time. The hybrid refrigeration system including LiBr absorption chiller and electric compression refrigerator provides cooling load to users. A multi-objective assessment and optimization synthetically considering energy, economy and environment are presented. The multi-objective indicator used as objective function to optimize each component capacity of the proposed CCHP system. A sensitive analysis of key parameters and performance comparison with conventional CCHP system have been carried out. The results shows that when the capacity of gas turbine is 691 kW, the comprehensive performance of the proposed CCHP system is the optimal performance. The power price, natural gas price, compression ratio and turbine inlet temperature of CAES have great influence on the performance of the proposed CCHP system. Meanwhile, the multi-objective indicator's value of the proposed CCHP system is more than conventional CCHP system 4.85%.